An efficient and combined placental T1‐ADC acquisition in pregnancies with and without pre‐eclampsia. Issue 5 (15th July 2021) - Hutter, Jana; Ho, Alison; Jackson, Laurence H.; Slator, Paddy J.; Chappell, Lucy C.; Hajnal, Joseph V.; Rutherford, Mary A.
Abstract : Purpose: To provide a new approach to jointly assess microstructural and molecular properties of the human placenta in vivo fast and efficiently and to present initial evidence in cohorts of healthy pregnancies and those affected by pre‐eclampsia. Methods: Slice and diffusion preparation shuffling, built on the previously proposed ZEBRA method, is presented as a robust and fast way to obtain T 1 and apparent diffusivity coefficient (ADC) values. Joint modeling and evaluation is performed on a cohort of healthy and pre‐eclamptic participants at 3T. Results: The datasets show the ability to obtain robust and fast T 1 ‐ADC measurements. Significant decay over gestation in T 1 (−11 ms/week, P < . 05 ) and a trend toward significance in ADC (−0.23 mm/ s 2 /week, P = .08) values can be observed in a control cohort. Values for the pre‐eclamptic pregnancies show a negative trend for both ADC and T 1 . Conclusions: The presented sequence allows the simultaneous acquisition of 2 of the most promising quantitative parameters to study placental insufficiency—identified individually as relevant in previous studies—in under 2 minutes. This allows dynamic assessment of physiological processes, reduced inconsistency in spatial comparisons due to reduced motion artefacts and opens novel avenues for analysis. Initial results in pre‐eclamptic placentas, with depicted changes in both ADC and T 1, illustrate its potential to identify cases of placental insufficiency. Future work will focus on expanding the field‐of‐view using multi‐band acceleration techniques and the expansion to larger and more diverse patient groups.